PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM), SISTEM PENGENDALIAN INTERNAL PEMERINTAH (SPIP), DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH - Latifatul Yaswat; Taufeni Taufik; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to determine the competence human resource, government internal control system, and the implementation offinancial accounting system on the effectiveness offinancial management area. This study using purposive sampling method. The population in this study servants Tanah Datar region, namely the head of department, chief financial officer, treasurer receipts and expenditures. Samples and this research is 88 respondents who have met the criteria for a sample. The collection data techniques used is by distributing questionnaires. The data were analyzed using multiple linear regression analysis with SPSS. Results of testing the hypothesis in this study indicate that the competence human resources, government internal control system and the implementation financial accounting systems significantly affect the effectiveness of financial management area.Keywords: competence, human resources, internal control system, financial accounting system, and effectiveness